TINJAUAN YURIDIS ATAS GUGURNYA HAK UNTUK MENUNTUT PIDANA MENURUT UNDANG-UNDANG HUKUM - Nur Cahya Dian Sahputra dan Syamsul Bahri (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
In order to complete studies at the University of Law Faculty of August 17, 1945 Samarinda, one of the tasks that must be completed is scientific writing, this imiah writing is entitled: "Juridical Review of the Fall of the Right to Prosecute under the Criminal Law Act". This scientific research method uses normative juridies.The violation of the right to sue is regulated in Chapter VII of the Criminal Code, while the violation of the right to sue is regulated in the Criminal Code, namely:The principle of "Ne bis in idem" (Article 76 of the Criminal Code).Death of the perpetrator (Article 77 of the Criminal Code).Expiry (Article 78 of the Criminal Code).Settlement of cases outside court trials (Article 82 of the Criminal Code).Amnesty and Abolition from the President (Article 14 of the 1945 Constitution).There are no complaints on complaints offenses.This provision contained in the Criminal Code is to provide legal certainty for the community specifically the perpetrators of criminal acts. Provisions for the cancellation of the right to sue are the duties and functions of the Attorney General's Office of the Republic of Indonesia based on Law 16 of 2004.The fall of the right to sue is caused by: 1) natural causes, 2) causes of human actions, and 3) legal causes It is hoped that the rules on the cancellation of the right to sue can be further emphasized in the new draft Law on Criminal Law (RKUHP) to provide legal certainty to the public. Likewise, cases of minor criminal acts (tipiring) should be resolved outside the court to avoid the accumulation of cases in court and the excess capacity of State Detention Centers or Penitentiaries.